Epstein–Barr Virus in Gliomas: Cause, Association, or Artifact? - Akhtar, Saghir; Vranic, Semir; Cyprian, Farhan Sachal; Al Moustafa, Ala-Eddin (Frontiers in Oncology, 2018)
Gliomas are the most common malignant brain tumours and account for around 60% of all primary central nervous system cancers. Glioblastoma multiforme (GBM) is a grade IV glioma associated with a poor outcome despite recent advances in chemotherapy. The aetiology of gliomas is unknown but neurotropic viruses including the Epstein-Barr virus (EBV) that is transmitted via salivary and genital fluids have been implicated recently. EBV is a member of the gamma herpes simplex family of DNA viruses that is known to cause infectious mononucleosis (glandular fever) and is strongly linked with the oncogenesis of several cancers including B-cell lymphomas, nasopharyngeal and gastric carcinomas. The fact that EBV is thought to be the causative agent for primary CNS lymphomas in immune-deficient patients has led to its investigations in other brain tumours including gliomas. Here we provide a review of the clinical literature pertaining to EBV in gliomas and discuss the possibilities of this virus being simply associative, causative or even an experimental artefact. We searched the PubMed/MEDLINE databases using the following key words such as: glioma(s), glioblastoma multiforme, brain tumors/cancers, Epstein-Barr Virus/EBV and neurotropic viruses. Our literature analysis indicates conflicting results on the presence and role of EBV in gliomas. Further comprehensive studies are needed to fully implicate EBV in gliomagenesis and oncomodulation. Understanding the role of EBV and other oncoviruses in the aetiology of gliomas, would likely open up new avenues for the treatment and management of these, often fatal, CNS tumours.